2006
DOI: 10.1128/ec.5.1.77-91.2006
|View full text |Cite
|
Sign up to set email alerts
|

Multigene Family Encoding 3′,5′-Cyclic-GMP-Dependent Protein Kinases in Paramecium tetraurelia Cells

Abstract: In the ciliate Paramecium tetraurelia, 3,5-cyclic GMP (cGMP) is one of the second messengers involved in several signal transduction pathways. The enzymes for its production and degradation are well established for these cells, whereas less is known about the potential effector proteins. On the basis of a current Paramecium genome project, we have identified a multigene family with at least 35 members, all of which encode cGMPdependent protein kinases (PKGs). They can be classified into 16 subfamilies with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Within this multigenic family, maintenance of genes during the successive genome duplications is in good agreement with expected behavior of genes subject to dosage constraints (highly expressed genes are preferentially retained as duplicates[ 9 ]). Most of the sub-groups observed in the epiplasmin family have a 4+2 topology, a distribution also described for other sets of highly expressed proteins: 35 cGMP-dependent protein kinases [ 19 ], 26 syntaxins [ 20 ], 12 synaptobrevins [ 21 ] and 17 vacuolar-proton-ATPases [ 22 ].…”
Section: Discussionmentioning
confidence: 86%
“…Within this multigenic family, maintenance of genes during the successive genome duplications is in good agreement with expected behavior of genes subject to dosage constraints (highly expressed genes are preferentially retained as duplicates[ 9 ]). Most of the sub-groups observed in the epiplasmin family have a 4+2 topology, a distribution also described for other sets of highly expressed proteins: 35 cGMP-dependent protein kinases [ 19 ], 26 syntaxins [ 20 ], 12 synaptobrevins [ 21 ] and 17 vacuolar-proton-ATPases [ 22 ].…”
Section: Discussionmentioning
confidence: 86%
“…The involvement of cGMP/PKG in membrane trafficking via interactions with SNARE proteins is also discussed by Kissmehl et al [21] and Yokoyama et al [22] but remains unexplored in TAL cells.…”
Section: Discussionmentioning
confidence: 95%
“…In the Paramecium cell cortex, any Ca 2 +-release channels would have to be located on the outer part of alveolar sacs, because the part facing the cell center is densely studded with Ca 2 +-pump molecules [56]. In agreement with this postulate, the subplasmalemmal space, including that delineated by alveolar sacs and trichocysts, is the site where pp63/pf [36], as well as the relevant protein phosphatase PP2B/CaN [42] and protein kinases CK-2 and PKG [57,58] are heavily enriched according to immuno-EM studies (see Fig. 1 and below).…”
Section: Introductionmentioning
confidence: 52%
“…Cloning and immunogold EM localisation revealed that guanylate cyclase is associated with the (ciliary and non-ciliary) cell membrane and the alveolar sacs membrane complex [63]. Interestingly this is also the distribution of the cGMP-activated protein kinase, PKG [58] (Fig. 1).…”
mentioning
confidence: 99%